Psychosocial Treatments for Cocaine Dependence: The Role of Depressive Symptoms - Stulz, Niklaus (2011)
BACKGROUND: The association between cocaine use and depression has been frequently observed. However, less is known about the significance of depression in the treatment of cocaine use disorders. This study examined possible interrelations between drug use and depression severity among cocaine-dependent patients in psychosocial treatments for cocaine dependence. METHODS: Monthly assessed drug use and depression severity scores of N = 487 patients during 6-month psychosocial treatments for cocaine dependence were analyzed using hybrid latent growth models. RESULTS: Results indicated a moderate but statistically significant (z = 3.13, p < .01) influence of depression severity on increased drug use in the upcoming month, whereas drug use did not affect future depression severity. CONCLUSIONS: Findings suggest that depression symptoms are an important predictor of drug use outcomes during psychosocial treatments for cocaine dependence and, hence, underline the importance of adequately addressing depression symptoms to improve treatment outcomes.